Factors Affecting Entrepreneurial Internship Effectiveness in it Industry: A Structural Equation Modeling - Chun-Mei, Chou; Chien-Hua, Shen; Hsi-Chi, Hsiao; Su-Chang, Chen (Review of Industrial Engineering Letters, 2014)
This study examines 324 tertiary students’ entrepreneurial internship effectiveness and its influencing factors in IT industry to serve as a school reference for the development of entrepreneurial internship education measures. The results show that students” “entrepreneurial intention (EI)” has a significant direct effect on “entrepreneurial internship effectiveness (EIE)”, and “internship satisfaction (IS) “has a significant effect on “entrepreneurial internship effectiveness” through “internship satisfaction.” The influence pattern and empirical data of “internship satisfaction” and “entrepreneurial intention” on “entrepreneurial internship effectiveness” has a good fit.